Pengembangan Geographic Information System (GIS) guna Pengelolaan Komoditas Tanaman Cabai - Karina Sukmawati; Amalia Rahmah (LPPM STT Terpadu Nurul Fikri, 2022)
This study focuses on implementing a geographic information system using ArcGIS 10.8 software to manage chili plantations in Clekatakan Village, Kab. Pemalang. The purpose of this study is the implementation of a geographic information system (GIS) for chili plantation management that can display the distribution of plantation area and design a GIS that has the feature of calculating chili production predictions in the following year, as well as knowing the results of the evaluation of the implementation of the system made. The development method used is the Rational Unified Process (RUP). This research is a mixed method, a combination of quantitative and qualitative research types. Qualitative research with a case study approach to design a GIS to be implemented. Quantitative analysis for processing production prediction data. To make predictions using the Double Exponential Smoothing Holt forecasting method. The result of this research is the presentation of plantation mapping information using Arcgis 10.8 for chili plantation management. The system evaluation results using the Black Box and User Acceptance Test (UAT) method conducted by the user stated that the system was successfully implemented and quite helpful for monitoring chili plantations in Clekatakan Village. The system created in this study succeeded in designing a map of the distribution of chili plantations and other information and predicting harvest times using ArcGIS Desktop 10.8 software. The production prediction feature has been successfully implemented in a different system, which is implemented in Microsoft Excel.